An Oatp transporter-mediated steroid sink promotes tumor-induced cachexia in Drosophila. - Santabárbara-Ruiz, P.; Léopold, P. (Developmental Cell, 2021)
Cancer cachexia is associated with many types of tumors and is characterized by a combination of anorexia, loss of body weight, catabolic alterations, and systemic inflammation. We developed a tumor model in Drosophila larvae that causies cachexia-like syndrome, and we found that cachectic larvae show reduced levels of the circulating steroid ecdysone (Ec). Artificially importing Ec in the tumor through the use of the EcI/Oatp74D importer aggravated cachexia, whereas feeding animals with Ec rescued cachectic defects. This suggests that a steroid sink induced by the tumor promotes catabolic alterations in healthy tissues. We found that Oatp33Eb, a member of the Oatp transporter family, is specifically induced in tumors promoting cachexia. The overexpression of Oatp33Eb in noncachectic tumors induced cachexia, whereas its inhibition in cachectic tumors restored circulating Ec and reversed cachectic alterations. Oatp transporters are induced in several types of hormone-dependent tumors, and this result suggests that a similar sink effect could modify hormonal balance in cachectic cancer patients.